Ethics and Learning Analytics: a necessary combination for scientific rigor (Práxis Educativa, 2023)
We live in a networked information society, which transcends physical and temporal spaces through the Internet and Information and Communication Technologies (ICT). This scenario produces data accumulation that can be analyzed for better decision making, aiming, in the educational field, to improve learning, using Learning Analytics (LA). Thus, the use of these data needs to be guided by well-defined ethical precepts, however, in the Brazilian reality, there are still gaps in the specific resolutions for the area of knowledge of the Human and Social Sciences (HSS), including the field of LA, a fact that generated this essay, which intended to interrelate ethical norms and the field of LA. In Brazil, Resolution no. 510/2016 regulates investigations in HSS, but its approach is superficial and there is no concern with research based on data collected digitally. Recently, the General Law for the Protection of Personal Data (Law no. 13.709/2018) demonstrates concern with this scenario, always in favor of scientific development, as provided for in the Code of Conduct for LA. Thus, despite being embryonic, the Brazilian initiative is already a step forward for researchers in the area to use data based on ethical and scientific rigor.Keywords: Human and Social Sciences. Education. Data analysis.